2012
DOI: 10.1007/s00340-012-5032-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-resolved potential measurement with ion crystals

Abstract: We present a method to measure potentials over an extended region using one-dimensional ion crystals in a radio frequency (RF) ion trap. The equilibrium spacings of the ions within the crystal allow the determination of the external forces acting at each point. From this the overall potential, and also potentials due to specific trap features, are calculated. The method can be used to probe potentials near proximal objects in real time, and can be generalized to higher dimensions.Comment: 7 pages (double space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The spatial derivatives ϕ ′ x ( ) i and ϕ″ x ( ) i are obtained by differentiation of the fit functions. Previous experiments have shown that the calculated potentials allow for the prediction of ion positions and trap frequencies with an accuracy of one per cent [28,29] which indicates the precision of the microtrap fabrication process. An increase in the precision can be achieved by calibrating the trapping potentials using resolved sideband spectroscopy.…”
Section: Prerequisitesmentioning
confidence: 84%
“…The spatial derivatives ϕ ′ x ( ) i and ϕ″ x ( ) i are obtained by differentiation of the fit functions. Previous experiments have shown that the calculated potentials allow for the prediction of ion positions and trap frequencies with an accuracy of one per cent [28,29] which indicates the precision of the microtrap fabrication process. An increase in the precision can be achieved by calibrating the trapping potentials using resolved sideband spectroscopy.…”
Section: Prerequisitesmentioning
confidence: 84%
“…Given the complexity of modeling trap geometries, and of changing the distance to the trapping electrodes, it may be advantageous to characterize the heating due to external objects which are independent of the trap operation. It has been proposed that this could be achieved by using an ion trap with an open geometry and varying the distance between it and some external object (Maiwald et al, 2009;Harlander et al, 2010;Brownnutt et al, 2012).…”
Section: Distancementioning
confidence: 99%
“…Modern trap technology [21,22], where the DC trap potential is shaped by multiple control segments, allows one to modify the trap potential along e z and thus the inter-ion distances. This becomes particularly relevant for crystals with ≥ 4 ions.…”
mentioning
confidence: 99%